Natural cryptic autoantibodies - Cheng, H.M. (Taylor & Francis, 1998)
Natural antibodies are commonly found in the blood circulation of normal individuals.[1] Their synthesis is thought to be independent of active or deliberate antigen immunization. The genes encoding the V regions of natural antibodies are unmutated in contrasts with frequent somatic mutations selectively accumulated in the complementarity determining regions of the specific antibodies induced in healthy individuals by immunization with foreign antigens and of the specific autoantibodies purified from patients with systemic and organ-specific autoimmune disorders.[2] The majority of natural autoantibodies have polyspecific binding properties and the target molecules recognized include both foreign and self-antigens.[2] The detection of natural antibody binding activity has increasingly been reported in isolated immunoglobulin fractions while in the whole normal human serum (NHS), the specific antibody reactivity is either low or not as frequently found.3 This strongly implies that a significant population of naturally-occurring antibodies are present in a cryptic form, masked by normal serum components.[4,5] This review will focus on such natural, cryptic autoantibodies (NcA) and will describe the antigen specificity, the isotypes, the masking serum coinhibitors and possible functional roles of NcA as reported in the literature.